PREVELENCE OF GIARDIASIS IN HUMAN AND DOGS - Mohammed, Talib, A.R.; Wali, Nabil A. (The Iraqi Journal of Veterinary Medicine, 2021)
From Ministry of Health records from 1989-1995, Giardiasis in human being was recorded between 4.3%-9.9%. In comparison between years 1988 and 1989 with 1994 and 1995 in Baghdad there was a double fold increase. The study followed up the disease in dogs.